Multimodality Treatment of Locally-Advanced Breast Cancer Using 6.3 MeV Fast Neutrons and Quality of Life in Patients in Long-Term Follow-Up; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Startseva Z. (Radiation Technologies in Medicine, 2015)
Title screen